Once an entrepreneur, always an entrepreneur? Entrepreneurial identity, job characteristics, and voluntary turnover of former entrepreneurs in paid employment - Feng, Jie; Allen, David G.; Seibert, Scott E. (Personnel psychology, 2022)
We focus on former entrepreneurs’ employment in established firms. Understanding the retention of former entrepreneurs—those who were previously founders of business ventures—is important to firms hoping to reap the benefits of their entrepreneurial experience. We compare the duration of their retention to other employees without entrepreneurial experience and propose a theoretical model in which entrepreneurial identity and job characteristics play a central role. The time‐dependent risk of voluntary turnover was estimated using survival analysis. Results from a primary survey collected from multiple firms in 2015–2018 (Study 1) reveal that former entrepreneurs quit sooner than others, and this effect was mediated by entrepreneurial identity. A second study using the NLSY79 and O*Net longitudinal dataset (Study 2) again supports this mediated relationship and further shows that the indirect effect through entrepreneurial identity was moderated such that employees with entrepreneurial identity stayed longer in jobs with favorable characteristics (i.e., high levels of work autonomy and more entrepreneurial opportunities) than other jobs. In Study 2, we were able to observe individuals’ careers over decades to capture the patterns of individual mobility—the back‐and‐forth exploration between businesses owned by self and others. The supplementary analysis provides additional evidence regarding turnover destinations. The findings offer implications for firms endeavoring to retain entrepreneurial talent and individuals pursuing a career that may involve both paid employment and entrepreneurship.